Bimbingan dan Pelatihan Penalaran Matematika Jenis Soal UTBK bagi Siswa SMA di Masa Pandemi Covid-19 - Justin Eduardo Simarmata; Zulkaidah Nur Ahzan (Universitas Mathla'ul Anwar Banten, 2021)
GUIDING AND TRAINING OF MATHEMATICAL REASONING: CBT QUESTIONS FOR HIGH SCHOOL STUDENTS DURING THE COVID-19 PANDEMIC. The spread of the Covid-19 outbreak in Indonesia has disrupted the education sector, especially in the learning process for high school students of class XII who will face various exams to enter state universities. The solution offered to continue the learning process during this pandemic is to carry out online distance learning from their residences. The purpose of this community service activity is ordering that student at SMA Negeri 1 Kefamenanu are able to recognize and master strategies to answer UTBK questions with mathematical reasoning, and solve these problems with good time management. This is very important, considering that students are not used to completing TKA and TPS UTBK questions during learning at school. The method of implementation in this community service activity is in the form of guidance and training for all students of class XII Science, XII Social Studies, and XII Language SMA Negeri 1 Kefamenanu. Activities are carried out in the form of guidance and training using an online system through the zoom application for one month. The online system is carried out in order to minimize the spread of Covid-19 among students. From the calculation results, it is obtained that the pre-test average is smaller than the post-test average so it can be concluded that guidance and training on mathematical reasoning for the types of UTBK questions has succeeded in improving better results for students, especially as preparation for facing UTBK, which results will be used to follow SBMPTN 2021. Besides that, the participation rate (attendance) of participants in each meeting is more than 90% of the total students.